If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5q + 2 = 37 Reorder the terms: 2 + 5q = 37 Solving 2 + 5q = 37 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 5q = 37 + -2 Combine like terms: 2 + -2 = 0 0 + 5q = 37 + -2 5q = 37 + -2 Combine like terms: 37 + -2 = 35 5q = 35 Divide each side by '5'. q = 7 Simplifying q = 7
| 4x^1/3=16 | | (26-6)=13n | | 2Y+24(24)=89 | | 16x^2+20x-200=0 | | 5/9u=20 | | 6z+18=5z+3 | | -9a=1 | | 6.3=(x*9.36)+(y*5.04) | | 6.3=(6.3-x*5.04)+(x*5.04) | | 6x+10=-95-9xs | | 56x-2=6+2x | | 4y+3=-2 | | m+5=-3 | | 3x(x^2+6x)= | | 19=5a+126b | | 2m+5=3m-7 | | 19=5a+12b | | x+4=2y-10 | | Cosx=.23 | | 4+x=5x-9-(2x-3) | | 0.6x+0.8=0.28x+1.16 | | 2x+21=16-3x | | (4x-3)-5=7 | | (x^4)-(2x^2)-1=0 | | (x+2)+(y-5)=8 | | Xlog=4 | | 5x+2y=2x-4y | | (4x)*(4x)+(x+1)*(x+1)=(5x-1)*(5x-1) | | 5x+12=30-9x | | 5x^6-16x^4-x^3-5=0 | | cotx+2=0 | | 4x+(x+1)=5x-1 |